Running economy in elite soccer and basketball players: differences among positions on the field - Boone, J.; Deprez, D.; Bourgois, J. (International Journal of Performance Analysis in Sport, 2014)
In the present study running economy (RE) was recorded in elite soccer and basketball players and positional differences were addressed. Elite soccer players (n=111) and basketball players (n=39), active in the Belgian first division performed an incremental running test (8 km. h-1 + 2 km. h-1 each three minutes) on a treadmill until exhaustion. Throughout the test gas exchange was registered and capillary blood samples were taken from which peak oxygen uptake (VO2 peak), speed at the anaerobic threshold (VAnT) and RE could be determined. These parameters were compared among the playing positions in soccer and basketball. In soccer, midfielders (214.4 ± 11.1 ml. km-1.kg-1) and full-backs (218.4 ± 10.3 ml. km-1.kg-1) had a significantly higher RE compared to center-backs (231.4 ± 8.8 ml. km-1.kg-1). In basketball, guards (229.4 ± 10.4 ml. km-1.kg-1) had a significantly higher RE compared to forwards (237.8 ± 9.3 ml. km-1.kg-1) and centers (243.3 ± 13.2 ml. km-1.kg-1). These differences in RE were accompanied by similar positional differences in VO2 peak and VAnT. Furthermore, both in soccer (R=0.56) and basketball (R=0.63), RE was correlated to VAnT. The present study points at the importance of RE in physical preparation of team sports and it can be concluded that teamsport-specific training should also focus on improving RE.